رچرڈ بیل اور آرتھر جیفری کے قرآن پر اعتراضات کا تنقیدی جائزہ : A CRITICAL ANALYSIS OF RICHARD BELL AND ARTHUR JEFFERY'S OBJECTIONS TO THE QURAN (Al-Aasar, 2025)
This paper critically explores the objections raised by prominent Orientalists, Richard Bell and Arthur Jeffery, against the Quran, probing their claims through an Islamic scholarly lens. Bell’s assertion that the Quran’s structure reflects human compilation rather than divine revelation and Jeffery’s skepticism about textual integrity and foreign linguistic influences are meticulously analyzed. The study investigates their arguments, contextualizing them within the broader Orientalist agenda to undermine the Quran’s divine authenticity, as highlighted by Edward Said’s critique of Western intellectual hegemony.The research systematically refutes these claims by drawing on classical and contemporary Islamic scholarship, including the works of Dr. Muhammad Hamidullah, Imam al-Suyuti, and Ibn Taymiyyah. It demonstrates how Bell’s theories on the Quran’s rearrangement lack historical evidence, while Jeffery’s emphasis on textual variants overlooks the Quran’s preservation through oral and written transmission. The paper also examines the theological and linguistic rebuttals to Jeffery’s assertion of non-Arabic vocabulary, affirming the Quran’s linguistic purity and miraculous eloquence.By engaging with primary Quranic texts, Hadith, and academic critiques, this study underscores the resilience of Islamic scholarship in countering Orientalist narratives. It ultimately reaffirms the Quran’s divine origin, its textual coherence, and the failure of external critiques to destabilize its foundational role in Muslim faith and practice. The analysis bridges historical and modern discourses, offering a robust defense of the Quran’s integrity against skeptical academia.